2020
DOI: 10.3390/agronomy10020184
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability of Quality Protein Maize Inbred Lines for Yield and Morpho-Agronomic Traits under Optimum as Well as Combined Drought and Heat-Stressed Conditions

Abstract: Drought and heat stress have perceptibly become major maize (Zea mays L.) yield reducing factors in Sub-Saharan Africa. As such, the objectives of this study were to: (i) determine the type of gene action conditioning tolerance to combined drought and heat stress (CDHS), and (ii) identify inbred lines with good combining ability for yield and other morpho-agronomic traits under CDHS. Twenty-four single cross hybrids (SCHs) obtained from crossing 10 inbred lines in a 4 × 6 North Carolina Design II, and a drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…These hybrids involved at least one high GCA parent, which could be exploited by conventional breeding procedures. This finding is in line with the result reported in other studies [ 56 , 59 ]. In their studies, high SCA was observed in cross combinations involving one line with high GCA and another with low GCA effects.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These hybrids involved at least one high GCA parent, which could be exploited by conventional breeding procedures. This finding is in line with the result reported in other studies [ 56 , 59 ]. In their studies, high SCA was observed in cross combinations involving one line with high GCA and another with low GCA effects.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, none of the inbred lines exhibited significant GCA effects for all the measured traits under any of the testing densities. Similar results were reported by other researchers [ 56 , 57 ]. The significant and negative GCA effects were displayed by the inbreds L 1 and L 3 for DTS and L 1 , L 2 and L 5 for ASI across the three plant densities, indicating that, these inbreds could be good combiners and possessed favorable alleles towards earliness.…”
Section: Discussionsupporting
confidence: 93%
“…Although maize is well adapted and substantially utilized in the savannas of SSA, the concurrent incidence of abiotic stresses such as drought and high temperature during flowering could reduce the photosynthetic rate, accelerate leaf senescence, induce kernel abortion and ultimately cause drastic yield losses [19,20]. The combination of the two stresses could lead to a grain yield loss of more than 90% during flowering and grain filling in maize [10,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, P4 can be crossed with P3 to create mapping population to use in identifying associated QTL's to heat tolerance with respect to total biomass, curling of leaves, CCI, root length, vigour and plant height [25]. Similar results were reported in previous studies were only desirable GCA effects among utilised germplasm with regards to height response to heat stress was obtained [26,27]. This implies that height is a high heritable trait which is less likely to be influenced by the environment when utilised for selection to heat stress.…”
Section: Fig 1 Principle Component Analysis Exhibiting Genotypes Inmentioning
confidence: 56%